A1_1 Making a house go ‘Up’! - Carr, Natasha; Harrison, Joseph; McCulloch, Ariella; Whitaker, Joshua (Physics Special Topics, 2022)
This paper will find that the number of helium balloons required to lift Carl’s house is around 456, 000 by using displacement and Archimedes’ Principle, therefore requiring over 20 times the amount of helium in Earth’s atmosphere. Continuing from this, the suggestion of using 423, 000 hydrogen balloons is made, as the synthesis of hydrogen via electrolysis of water could provide the 48,000 m3 of the gas.